The Role of Teaching Christian Religious Education against Domestic Violence - Elys Lusiari Papuana Toam (Syntax Corporation Indonesia, 2022)
Every year, more cases of violence against women and children are reported. According to the poll done by the Ministry of Women's Empowerment, the average age of children and women in 2021 was between 15 and 64 years. This rose from prior years. The rise in cases in 2021 is a warning not only to the government, in this example, the Ministry or State Institution, but to all community institutions. This study aims to establish the role of Christian religious education in preventing domestic violence and utilizing qualitative methodologies. The study's findings imply that Christian religious education must incorporate pre-marriage marriage consultations and a curriculum emphasizing the significance of protecting women and children in the family and social life.